The Complexity of Determining Indicative Evidence in The Rape Criminal Act - Ni Putu Rai Yuliartini; Wita Setyaningrum; Dewa Gede Sudika Mangku (Fakultas Hukum Universitas Muhammadiyah Magelang, 2021)
The rise of rape cases in Indonesia has resulted in social unrest, especially among women and children. Sometimes, judges have difficulty determining indicative evidence of rape cases. This study aims to analyze the strength of the evidence as consideration for judges in the criminal case of rape. This research is normative legal research. The data used in this research is secondary data obtained through a literature study and analyzed juridically normative based on a statutory and conceptual approach. The legal materials used in this research are primary and secondary legal materials. The study results show that rape is the most difficult crime to prove, considering that this kind of crime is often committed in places where it is difficult to find witnesses. Judges experience difficulties in concretely explaining evidence. Even in court practice often experience difficulties in applying it. These difficulties can then have implications for the decision that the judge will release because the decision is dominated by the judge's verdict, which may be excessive. Indicative evidence is the only indirect evidence among other evidence formulated in Article 184 of the Criminal Procedure Code.